The practices of human resource management among headmasters in primary schools : a case study of selected national and private schools in Malaysia - Najla Aiman binti Mohamed Idrus (Kulliyyah of Education, International Islamic University Malaysia, 2017)
This study focuses on the practices of human resource management among headmasters in primary schools across Malaysia. It concentrates on how headmasters perceive the concept of human resource management and translate it into practice. The qualitative research design is applied on six headmasters, four males and two females who serve in selected national and private primary schools. The qualitative data from the interviews are organized into themes and sub-themes. The major findings of this study reveal that a majority of the headmasters perceive human resource management as a shared responsibility among teachers and school administrators while the headmaster is the key manager. It also reveals that headmasters in national schools believe that human resource management is important to reach the educational goal. In contrast, a majority of headmasters in private schools believe that it is important for sustainability. In addition, this study also reveals that the headmasters of national schools have less autonomy in decision-making process as compared to headmasters of private schools. The results have implications on two major aspects; the leadership in human resource management and the system. The leadership implication will help headmasters identify the best practices of human resource management including support and professional development for the teachers. System refers to teacher placement and other policy implementation. Finally, this study recommends more authority to be given to headmasters in managing human resource in schools, especially in the national schools.